Pengaruh Citra Merek Promosi dan Kepercayaan terhadap Keputusan Pembelian Konsumen di Tokopedia (Studi Kasus Penduduk Muaro Jambi) - Mappadeceng, Riko; Tarmizi, Ahmad; Apriyanti, Lily (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The growth and development of technology plays a major role in people's lives in this modern era. The growth and development of technology are utilized by the business world as a means of product promotion and sales. Consumers utilize this technology by buying or selling goods or services online. To answer the research objectives, the author uses a theoretical study related to the research variables, namely brand image, promotion, trust and purchasing decisions. In addition, the author also looked for relevant previous research in the form of journals/articles and previous theses to support this research. This study used 100 respondents with analysis techniques using multiple linear regression and hypothesis testing using the f test and t test. The type of data used in this study is quantitative descriptive. Regression aims to test the relationship of the influence of one variable, the variable that is influenced is called the dependent variable, while the variable that influences is called the independent variable. The object of this research is Tokopedia. Tokopedia is one of the largest digital-based shopping companies in Indonesia. Since its official launch, Tokopedia has succeeded in becoming one of Indonesia's internet companies with rapid growth. By carrying the marketplace and online mall business model, Tokopedia allows every individual, small shop, or brand to open and manage an online shop. From the results of data processing, the regression equation Y = 0.933 + 0.135X1 + 0.291X2 + 0.299X3. Meanwhile, from the hypothesis testing conducted, the results of the study showed that brand image, promotion and trust have a positive and significant effect on purchasing decisions simultaneously and partially. The results of the research, data analysis and discussion in this study can be concluded that brand image, promotion, trust and purchasing decisions on Tokopedia are in very good condition. The influence of brand image, promotion and trust on purchasing decisions is 48.80%